2019
DOI: 10.3389/fmicb.2019.00248
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Planktonic Freshwater Ciliates: Are Analyses Based on V9 Regions of the 18S rRNA Gene Correlated With Morphospecies Counts?

Abstract: Ciliates represent central nodes in freshwater planktonic food webs, and many species show pronounced seasonality, with short-lived maxima of a few dominant taxa while many being rare or ephemeral. These observations are primarily based on morphospecies counting methods, which, however, have limitations concerning the amount and volume of samples that can be processed. For high sampling frequencies at large scales, high throughput sequencing (HTS) of freshwater ciliates seems to be a promising tool. However, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 75 publications
2
56
0
Order By: Relevance
“…Comparison of composition at lower taxonomic levels as revealed by the two approaches therefore becomes inappropriate and inaccurate under these circumstances. This also corresponds with the findings of previous studies where both methods have been applied, i.e., on tintinnid ciliates from coastal waters (Bachy et al, 2013; Santoferrara et al, 2014) or planktonic ciliates from mountain lakes (Stoeck et al, 2014; Pitsch et al, 2019), which have also reported a gap between molecular and morphological methods for revealing community composition at lower taxonomic ranks.…”
Section: Discussionsupporting
confidence: 90%
“…Comparison of composition at lower taxonomic levels as revealed by the two approaches therefore becomes inappropriate and inaccurate under these circumstances. This also corresponds with the findings of previous studies where both methods have been applied, i.e., on tintinnid ciliates from coastal waters (Bachy et al, 2013; Santoferrara et al, 2014) or planktonic ciliates from mountain lakes (Stoeck et al, 2014; Pitsch et al, 2019), which have also reported a gap between molecular and morphological methods for revealing community composition at lower taxonomic ranks.…”
Section: Discussionsupporting
confidence: 90%
“…The V9 region of the 18S rRNA gene was targeted with the 1389F/1510R primers described by Amaral-Zettler et al (2009), and widely used in ecological studies for the investigation of eukaryotic diversity (e.g., de Vargas et al, 2015; Sawaya et al, 2019; Pitsch et al, 2019). Primers were modified at the 5′ end to include overhang sequences (Illumina adapters) for the downstream sequencing (forward overhang (37 bp): 5′-ATCTACACTCTTTCCCTACACGACGCTCTTCCGATCT-3′; reverse overhang (34 bp): 5′-GTGACTGGAGTTCAGACGTGTGCTCTTCCGATCT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…) or for tracking the distribution of particular lineages in space and time (Pitsch et al. ; Santoferrara et al. ).…”
Section: What Have We Learned With and About Metabarcoding?mentioning
confidence: 99%